Desarrollo de una aplicación web multiplataforma de gestión y seguimiento de pedidos para la empresa textil IKERANY - Chamba Saca, Diego Jhonatan (2023)
This project aims to develop a web application to optimize the management and monitoring at the time of placing orders at IKERANY textile company, therefore, it is proposed to develop a software application that lets to take control of the process of receiving and delivering an order to its customers through a multiplatform web application, generating reports and notifications from its ingress to its departure of orders. For the development, it was chosen to use the AUP methodology, using the approach to assign tasks and responsibilities within a development organization, which allowed the production of a higher quality software. With the development of this project, the process of tracking and management of orders was improved, thus giving the possibility of keeping a record of customers and generated work orders. It was possible to process based on registered orders, giving priority to urgent orders. On the other hand, it was possible to print a work order at the time of making an ingress to control each one of the stages that must be accomplished until the end of production and control each of the credits that are made to complete the total payment of the order. Following all this process it was achieved to offer better attention to clients and rentability increase. Keywords. - Pwa, XAMPP, multiplatform, Front end, Back End, DOM.